Aksesibilitas Belanja Online Di Era Society 5.0 (Studi Kasus: Mahasiswa Jurusan Akuntansi Syariah) - Ieda Rizqi Rachmawati (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research deals with the accessibility of online shopping in the era of society 5.0. E-Commerce is electronic commerce related to buying, selling, marketing of goods or services by utilizing internet communication networks as a form of future commerce. The banking world has also been affected by the Covid-19 pandemic. Therefore the purpose of this study is to find out about the accessibility of online shopping in the era of society 5.0 for students. . The accessibility of online shopping has experienced a significant increase in the Society 5.0 era. Advances in technology and the spread of the internet have made it possible for people to access online shopping platforms easily and quickly. This provides an opportunity for individuals from various backgrounds to purchase products and services online. With this website, it is very easy and shortens the time when shopping online and makes it easy for students to be able to make transactions according to their wishes. It is also very practical to pay using a debit card, credit card, PayPal, check, or COD (Cash On Delivery), which is a payment made when the item has been sent by the seller. Consumer purchases are influenced by four main psychological factors including motivation, perception, learning, and beliefs and ideals. The sampling technique is a literature review from several references. This study uses an observational analysis of students when they use online shopping platforms.